"As Time Went On, I Just Forgot About It": Thematic Analysis of Spontaneous Disclosures of Recovered Memories of Childhood Sexual Abuse. Issue 1 (2nd January 2016) - MacIntosh, Heather B.; Fletcher, Kara; Collin-Vézina, Delphine
Abstract: This study was a thematic analysis of transcripts of interviews of child sexual abuse survivors discussing their experiences of recovered memories. This study included 27 English-speaking participants from 3 major Canadian cities: Montreal, Toronto, and Ottawa. Seven participants identified as male and 20 as female. Participants ranged in age from 31 to 69 with a mean age of 47. The educational background of participants ranged from 9th grade to doctoral levels. Out of the sample of 27, 21 participants reported some period of amnesia for their CSA experiences. Three primary global themes emerged in the transcripts of participants describing adult emergent recovered memories: flashbacks, triggers, and denial. Three global themes emerged in the transcripts of participants describing partially discontinuous memories: dreams/nightmares as the "how" of memory recovery, triggers, and active processes of forgetting.